Asuhan Keperawatan pada Pasien Preoperatif Pterigium - I Made Widastra; I Made Mertha; I Made Oka Bagiarta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
The aim of this study is to describe preoperative nursing care for patient with pterygium in Indera Hospital Denpasar. This study uses a descriptive research design with cross sectional approach. The method used to determine the sample is non-probability sampling is purposive sampling with a sample obtained by 45 patients. This study was conducted in May-June 2013 at Indera Hospital Denpasar. The results of this study is that the assessment of patient with pterygium in preoperative nursing care majority is Good (77.5%). At diagnosis, the majority value is Enough (60%). In the intervention, the majority value is Good (80%), as well as the implementation and evaluation of the majority value is Good (100%), and the majority value for nursing care for patient with pterygium is Good (83,5%).